Idiopathic Intracranial Hypertension With Unusual Presentation in an Adolescent Girl: A Case Report - Afagh Hassanzadeh Rad; Vahid Aminzadeh (Caspian Journal of Neurological Sciences, 2024)
Background: Idiopathic intracranial hypertension (IIH) or pseudotumor cerebri is a rare disorder. Regarding the latest diagnostic criteria for this disorder, we present a rare case of IIH. Case presentation: The case was an 11-year-old girl referred to our center with generalized body pain and mild left-eye deviation with no other visual symptoms. She had a severe generalized pain especially in her back and prevertebral area. In the neurological examination, there was a mild left sixth nerve palsy and bilateral papilledema. We treated the patient with acetazolamide and to lumbar puncture, which reduced intracranial pressure. The generalized body pain was reduced gradually in ten days, eye deviation in three weeks, and papilledema in two months after treatment. Conclusion: Based on the serious complications of IIH, a thorough assessment of suspicious cases, including ophthalmoscopic examinations, is mandatory. Furthermore, clinicians should consider even rare and unknown specific symptoms in these patients.